REGULATORY UNCERTAINTY IN CLIMATE REPORTING AND ITS IMPACT ON THE QUALITY OF FINANCIAL AND NON-FINANCIAL DISCLOSURES (American Journal of Technology and Applied Sciences, 2023)
This article analyzes the impact of regulatory uncertainty in climate reporting on the quality of companies' financial and non-financial disclosures. It examines the main sources of uncertainty, including differences in national implementation of international standards, political and legal disputes, and transition periods for implementing new requirements. Based on theoretical approaches to the economics of disclosure and a review of modern empirical research, it is shown that high regulatory uncertainty reduces the comparability and verifiability of climate disclosures, increases the subjectivity of assessments, and weakens the link between non-financial information and financial performance.